Aortic rupture during STABILISE (stent-assisted balloon-induced intimal disruption and relamination in aortic dissection repair) technique - Ashley C. Hsu, MD; Alexander D. DiBartolomeo, MD; Sukgu M. Han, MD, MS; Fernando Fleischman, MD; Gregory A. Magee, MD, MSc (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
The STABILISE (stent-assisted balloon-induced intimal disruption and relamination in aortic dissection repair) technique has shown promising results for treating type B aortic dissections, but the potential exists for fatal adverse effects. We present a case of infrarenal aortic rupture while using a compliant balloon to balloon mold the true lumen inside previously placed bare metal stents during the STABILISE technique. Caution is advised for providers who wish to perform the STABILISE technique, and we recommend using a semi-compliant balloon sized to the smallest total aortic diameter to mitigate the risk of rupture.